Implementation of The Concept of 'Urf and Maslahah in Buying and Selling Gold With Non-Cash Payment (Comparative Study of Fatwa DSN-MUI and Fatwa Al-Lajnah Ad Dāimah Li Al-Buhūṡ Al-‘Ilmiyyah Wa Al-Iftā’ Saudi Arabia) - Jauhari, Wildan; Abd Muhaimin, Abd Wahab; Arif Khan, Muhammad Dawud (Universitas Muhammadiyah Surakarta, 2023)
The background of writing this research is to respond to differences in fatwas that occurred in two major fatwa institutions, namely the National Sharia Council of the Indonesian Ulema Council and Al-Lajnah Ad-Dāimah Li Al-Buhūṡ Al-'Ilmiyyah Wa Al-Iftā' State of Saudi Arabia; in the law of buying and selling gold in cash. This difference in fatwas confused the public and required descriptions and explanations regarding the methodology used by the two fatwa institutions. In this study, the authors used a qualitative method as a case study with a normative juridical approach. The results of this study are that the National Sharia Council of the Indonesian Ulema Council allows buying and selling gold in cash, either through ordinary buying and selling or buying and selling murabaha, as long as gold does not become the official medium of exchange (money). As for the fatwa of Al-Lajnah Ad-Dāimah Li Al-Buhūṡ Al-'Ilmiyyah Wa Al-Iftā' number 3211, it states that delaying the payment of gold is not permitted if it is exchanged for gold, silver, or equivalent (money).